A Study on the improvement plan of long-term care insurance : focused on the efficient expenditure - Yoon, Sung-Joo (The Korea Institute of Public Finance SeoulKR, 2013)
Examines measures for more efficient spending for the elderly long-term care insurance in relation to two aspects : performance-based differentiation of grants for long-term care institutions, and usage-based differentiation of the patient's cost burden.